The modern researcher - Barzun, Jacques (Harcourt Brace Jovanovich, 1977)
This classic introduction to the techniques of research and the art of expression is used widely in historiography courses in many departments other than history. This book thoroughly covers every aspect of research from the selection of a topic, through the methods of finding and verifying data, writing and revising, to preparing a manuscript for publication.